Ashes on the moor [large type] - Eden, Sarah M. (Thorndike Press large print clean reads, 2019)
"After the death of her parents, Evangeline must succeed as a schoolteacher in a remote region of Northern England in order to claim her inheritance from her grandfather and be reunited with her younger sister, Lucy. When a local bricklayer, Dermot, offers his help, she finds herself falling in love with the Irishman"--Provided by publisher.